0368 Efficacy and Tolerability of Lemborexant in Female and Male Subjects with Insomnia. (12th April 2019) - Moline, Margaret; Murphy, Patricia; Yardley, Jane; Kumar, Dinesh; Pinner, Kate; Perdomo, Carlos; Rosenberg, Russell; Zammit, Gary
Abstract: Introduction: In clinical trials, efficacy and tolerability are typically evaluated in subgroups, including by sex. This report presents pooled analyses of subject-reported sleep onset latency (sSOL) and wake after sleep onset (sWASO) from lemborexant (LEM; dual orexin receptor antagonist) Phase 3 studies, SUNRISE-1 and -2. Methods: SUNRISE-1 was a 1-month, double-blind, placebo (PBO)- and active-controlled (zolpidem tartrate extended-release [SUNRISE-1 only]; not reported), parallel-group study in 1006 female and male subjects with insomnia disorder (age: females ≥55y, males ≥65y). SUNRISE-2 was a 6-month PBO-controlled, 6-month active treatment, double-blind, parallel-group study in 959 female and male subjects with insomnia disorder (age ≥18y). These analyses included subjects randomized to PBO, LEM 5mg (LEM5) or LEM 10mg (LEM10). Each study included a single-blind PBO run-in prior to randomization. Results: This pooled analysis included 402 (23.7%) male and 1291 (76.3%) female subjects. Results on sSOL and sWASO were consistent with the significant results on sleep diary in the individual studies. In both sexes, sSOL was significantly reduced versus PBO for LEM5 and LEM10 during the first 7 days and end of Month 1 (P<0.05 all comparisons). In females, there were significantly greater reductions in sWASO versus PBO for both LEM doses (first 7 days and end of Month 1; P<0.0001 all comparisons). In males, sWASO decreased significantly compared with PBO for the first 7 days (LEM5 and LEM10; P≤0.0001) and end of Month 1 (LEM10 only; P=0.0032). For PBO, LEM5 and LEM10, overall incidence of TEAEs was similar across sexes. Incidence of treatment-emergent serious AEs was low for both subgroups; most events occurred in 1 subject each. TEAEs leading to study drug withdrawal or interruption were few and similar across sexes for all treatments. Somnolence incidence, the most frequent TEAE, was consistent between sexes. Approximately 3% of females (0 males) reported urinary tract infection; incidence in females was similar across treatment groups. Conclusion: LEM effectively treats both sleep onset and maintenance variables in male and female subjects with insomnia, and is well-tolerated by both sexes. Support (If Any): Eisai, Inc., Purdue Pharma L.P.